Sammankoppling av fjärrvärmenäten i Nyköping och Oxelösund : miljö- och systemkonsekvenser - Lindow, Veronica (SLU/Dept. of Energy and Technology, 2009)
District heating covers most of the residential areas and industries in the two neighbouring Swedish municipalities Nyköping and Oxelösund. In Nyköping, Vattenfall AB Värme produces heat in a bio-fuelled CHP plant. In Oxelösund, waste heat and use of waste gases from the steel production at SSAB Oxelösund is the basis in the district heating system.